Condition monitoring philosophy for tidal turbines - Elasha, Faris; Mba, David; Amaral Teixeira, Joao (RAMS Consultants, 2014)
Renewable energy is currently considered as the main solution to reduce greenhouse gas emission. This has led to great developments in the use of renewable energy for electricity generation. Among many renewable energy resources, tidal energy has the advantage of being predictable, particularly when compared to wind energy. Currently the UK is the world leader in extracting energy from the tide; an estimation shows a potential of 67 TWh per year. In order to ensure safe operation and prolonged life for tidal turbines, condition monitoring is essential. The technology for power generation using tidal turbines is new therefore the condition monitoring concept for these devices is yet to be established. Also, there is a lack of understanding of techniques suitable for health monitoring of the turbine components and support structure given their unique operating environment.In this paper the condition monitoring of a tidal turbine is investigated. The objective is to highlight the need for condition monitoring and establish procedures to decide the condition monitoring techniques required, in addition to highlighting the impact and benefits of applying condition based maintenance. A model for failure analysis is developed to assess the needs for condition monitoring and identify critical components, after which a ‘symptoms analysis’ was performed to decide the appropriate condition monitoring techniques. Finally, the impact of condition monitoring on system reliability is considered.
Keywords: Greenhouse gases; Tidal power; Turbines; Wind power; Renewable energies; Support structures; Operating environment